The effectiveness of immediate versus delayed tubal flushing with oil-based contrast in women with unexplained infertility (H2Oil-timing study): study protocol of a randomized controlled trial - D. Kamphuis; K. Rosielle; N. van Welie; I. Roest; A. J.C.M. van Dongen; E. A. Brinkhuis; P. Bourdrez; A. Mozes; H. R. Verhoeve; D. P. van der Ham; F. P.J.M. Vrouenraets; J. J. Risseeuw; et al. (BMC, 2023)
Abstract Background In women with unexplained infertility, tubal flushing with oil-based contrast during hysterosalpingography leads to significantly more live births as compared to tubal flushing with water-based contrast during hysterosalpingography. However, it is unknown whether incorporating tubal flushing with oil-based contrast in the initial fertility work-up results to a reduced time to conception leading to live birth when compared to delayed tubal flushing that is performed six months after the initial fertility work-up. We also aim to evaluate the effectiveness of tubal flushing with oil-based contrast during hysterosalpingography versus no tubal flushing in the first six months of the study. Methods This study will be an investigator-initiated, open-label, international, multicenter, randomized controlled trial with a planned economic analysis alongside the study. Infertile women between 18 and 39 years of age, who have an ovulatory cycle, who are at low risk for tubal pathology and have been advised expectant management for at least six months (based on the Hunault prediction score) will be included in this study. Eligible women will be randomly allocated (1:1) to immediate tubal flushing (intervention) versus delayed tubal flushing (control group) by using web-based block randomization stratified per study center. The primary outcome is time to conception leading to live birth with conception within twelve months after randomization. We assess the cumulative conception rate at six and twelve months as two co-primary outcomes. Secondary outcomes include ongoing pregnancy rate, live birth rate, miscarriage rate, ectopic pregnancy rate, number of complications, procedural pain score and cost-effectiveness. To demonstrate or refute a shorter time to pregnancy of three months with a power of 90%, a sample size of 554 women is calculated. Discussion The H2Oil-timing study will provide insight into whether tubal flushing with oil-based contrast during hysterosalpingography should be incorporated in the initial fertility work-up in women with unexplained infertility as a therapeutic procedure. If this multicenter RCT shows that tubal flushing with oil-based contrast incorporated in the initial fertility work-up reduces time to conception and is a cost-effective strategy, the results may lead to adjustments of (inter)national guidelines and change clinical practice. Trial registration number The study was prospectively registered in International Clinical Trials Registry Platform (Main ID: EUCTR2018-004153-24-NL).